Medicinally important trees - Khan, Aisha S. (Springer Nature, 2017)
"This book provides researchers and advanced students associated with plant and pharmaceutical sciences with comprehensive information on medicinal trees, including their identification, morphological characteristics, traditional and economic uses, along with the latest research on their medicinal compounds. The text covers the ecological distribution of over 150 trees, which are characterized mainly on the basis of their unique properties and phytochemicals of medicinal importance (i.e., anti-allergic, anti-diabetic, anti-carcinogenic, anti-microbial, and possible anti-HIV compounds). Due to the incredibly large diversity of medicinal trees, it is not possible to cover all within one publication, so trees with unique medicinal properties that are relatively more common in many countries are discussed here in order to make it most informative for a global audience. With over 100 illustrations taken at different stages of plant development, this reference work serves as a tool for tree identification and provides morphological explanations. It includes the latest botanical research, including biochemical advancements in phytochemistry techniques such as chromatographic and spectrometric techniques. In addition, the end of each chapter presents the most up-to-date references for further sources of exploration."--Provided by publisher.
Keywords: Medicinal plants.; Botany, Medical.; Trees.; elektronické knihy; electronic books